The bilateral agreement between Ecuador and Peru: an analysis from the perspective of commercial and tourism development in the period 2016-2020 - Sánchez Alay, María Alexandra (Revista Universidad de Guayaquil, 2022)
The main objective of this research has focused on determining the impact of the Bilateral Agreement between Ecuador-Peru in the commercial and tourism sector, during the period 2016-2020, in order to propose strategies to encourage development and integration actions between both countries, from the perspective of social constructivism in international relations. It also sought to describe the integration initiatives established in said agreement and examine the barriers that have been generated in the commercial and tourism sector. For the development of this work, a series of theories were reviewed that allowed addressing the variables contemplated, their dimensions and indicators, as well as expanding knowledge about international border relations. The study was developed under a constructivist approach, using the Historical-Logical method, from a qualitative and documentary research. Observation was used as an information collection technique and a semi-structured interview was applied to three (3) experts in the commercial and tourist area, which allowed us to delve into the problem of the barriers that exist in the commercial and tourist sector that do not have allowed a prosperous development of the Agreement signed between the two countries. The results obtained allowed us to verify, based on the opinions of the interviewed experts, that despite the fact that relations between Ecuador and Peru have experienced great progress, there are still barriers that do not allow the expected development, mainly considering the historical and cultural barriers. that they still persist as a result of the great periods of disputes between both countries, trade barriers that have brought with them illicit activities and lack of control in the prices of the products that are marketed at the border level; and tourism barriers as a result of the lack of an effective binational structure to promote this sector.
Keywords: Bilateral Agreement; International Relations; Commercial and Tourism Development